CCDC25 may be a potential diagnostic and prognostic marker of hepatocellular carcinoma: Results from microarray analysis - Deng, Hongyang; Zhang, Jiaxing; Zheng, Yijun; Li, Jipin; Xiao, Qi; Wei, Fengxian; Han, Wei; Xu, Xiaodong; Zhang, Youcheng (Frontiers in Surgery, 2022)
Background: Hepatocellular carcinoma (HCC) is a type of cancer with high recurrence rate, poor prognosis and rapid progression. It is necessary to find out a novel biomarker in HCC. Coiled-coil domain containing 25 (CCDC25) was recently identified as a target molecule that mediates liver metastasis in colon cancer. However, the potential role of CCDC25 in HCC is unknown. Therefore, we aimed to explore the functions of CCDC25 in HCC. Methods: We used multiple databases to analyze the expression, relationship with prognosis, clinical data, methylation site, co-expressed genes, gene set enrichment analysis, and relationship with ferroptosis in HCC through bioinformatics. R-4.1.2 was applied to tidy data, functional enrichment analysis and evaluate immune infiltrates, diagnostic ability, Sorafenib IC50. Results: CCDC25 had a low expression in HCC samples and it has excellent diagnostic ability. Decreased CCDC25 was prominently associated with unfavorable survival. CIBERSORT analysis indicated that CCDC25 expression were significantly correlated with B cells memory, B cells native, dendritic cells activated, macrophages M0, macrophages M2, plasma cells, and T cells regulatory (Tregs). Furthermore, we found that CCDC25 expression was associated with immune checkpoints and ferroptosis key enzymes. Functional enrichment analysis revealed that CCDC25 regulates HCC progression though variety of cancer-related signaling pathways. Conclusions: CCDC25 associate with prognosis, diagnostic, ferroptosis and immune infiltration and may be a potential specific biomarker in HCC. Keywords: Coiled-coil domain containing 25, hepatocellular carcinoma, prognosis, diagnosis, immune infiltrates, ferroptosis